Moving policy to practice: role of advocacy in enabling provision of injectable contraceptives by pharmacists in Kenya - Njiri, Sally; Mulyanga, Sam; Choge, Irene; Kwachi, Beatrice; Mwalimu, Rammah; Ontiri, Susan (Frontiers in Global Women's Health, 2023)
Expanding access to contraceptive services by making them available in pharmacies and drug shops is a family planning high-impact practice. In 2018, Kenya's Ministry of Health amended its family planning guidelines to allow pharmacists and pharmaceutical technologists throughout the country to provide subcutaneous and intramuscular depot medroxyprogesterone acetate. Amending the policy did not necessarily mean that the policy would be implemented. The Advance Family Planning project launched an advocacy campaign to engage key stakeholders to work with the Ministry of Health to implement the policy. Consequently, a family planning training package for pharmacists and pharmaceutical technologists was developed and rolled out. The advocacy process also led to strengthening family planning reporting by the trained pharmacists and pharmaceutical technologists. To further enhance sustainability by ensuring a continuous pool of pharmacy professionals equipped with skills to provide family planning services, Advance Family Planning and its partners advocated with universities and the Pharmacy and Poisons Board to revise the pre-service training curriculum to include family planning as a competence area for pharmacists and pharmaceutical technologists. A key lesson learned is that policy formulation does not necessarily translate to policy implementation. Advocacy is often needed to move policy to practice, especially where resources are required. Policy implementation also requires incremental achievement of milestones and the need for advocacy for each step in the process. Implementation of the policy provision that allows pharmacists and pharmaceutical technologists to provide injectable contraceptives has implications beyond family planning programs. It provides a point of reference for allowing pharmacists to offer other primary health care services, such as immunization, injectable HIV prophylaxis, and other interventions that might not be provided for in policy.